Community-Based Participatory Action Research Methodology To Improve Financial Literacy And Financial Inclusion Of Women Entrepreuner - Dian S. P. Koesoemasari; Sri Lestari; Harsuti Harsuti; Mayla Surveyandini; Diva Aulia Putri; Mutiara Naomi Juliantika; Juvita Ananda Putri (Green Publisher Indonesia, 2024)
Financial literacy and financial inclusion are indispensable for business actors, especially women entrepreneurs. Financial literacy is financial knowledge related to the ability to manage finances, such as making budgets, interest rate knowledge, investments, savings, and so on. Meanwhile, financial inclusion is the availability of access to financial institutions, financial products and services. Until now, there is still a gap in knowledge and financial inclusion among business actors, especially women entrepreneurs, towards financial technology. If business actors have good financial literacy and financial inclusion, they can take advantage of financial technology services for the sustainability of their business. The target group for this community service is a women's business group that is a member of the Banyumas micro small and small entrepreneurs association (ASPIKMAS) in Cilongok District. There were 30 counseling participants. Counseling is carried out face-to-face. The result of this activity is that women entrepreneurs are more familiar with financial technology services and can choose the right services needed to ensure the sustainability of their business.